Developing mobile application for Jabatan Pertahanan Awam Malaysia (JPAM) using agile unified process methodology with como mobile application builder / Fazli Abdul Hamid - Abdul Hamid, Fazli (2014)
MyJPAMCOMO, a mobile application or mobile app, has been introduced to enhance the notification delivery services by JPAM Putrajaya focuses on courses and training information for Putrajaya's force. Research has been done to find out the right methodology and the best software to develop the mobile app. The project would implement a methodology that is adaptable, flexible, and simple. The developer software has been selected with strictly no coding permissible. The software provides customization with pre-formatted features, colors, and layouts. The mobile app would retrieve its data from Google Calendar database. The data administrator merely enters courses and training data into the Calendar and it will automatically link to the mobile app. The outcome of this project is expectedly to enhance the delivery service and make the information available to everyone extensively and fast. At the moment, the software is having limited customization functionality and interfaces due to the software capability. In some way, the software is still the best for solo developer with little programming skill to develop mobile app in short time.